2014
DOI: 10.1002/2013ja019435
|View full text |Cite
|
Sign up to set email alerts
|

The quiet evening auroral arc and the structure of the growth phase near‐Earth plasma sheet

Abstract: The plasma pressure and current configuration of the near-Earth plasma sheet that creates and sustains the quiet evening auroral arc during the growth phase of magnetospheric substorms is investigated. We propose that the quiet evening arc (QEA) connects to the thin near-Earth current sheet, which forms during the development of the growth phase enhancement of convection. The current sheet's large polarization electric fields are shielded from the ionosphere by an Inverted-V parallel potential drop, thereby pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The groundbased observations have shown that the thickness is ~ 3.5 km at 200-km altitude (Dahlgren et al 2009). The arcs are called evening anticorrelation arcs (Marklund 1984), growth phase arcs (Haerendel 2010;Lyons et al 2011;, preexisting arcs (Jiang et al 2012), and quiet evening arcs (Coroniti and Pritchett 2014). Hereinafter, we refer it to as a quiet arc.…”
Section: Growth Phasementioning
confidence: 99%
“…The groundbased observations have shown that the thickness is ~ 3.5 km at 200-km altitude (Dahlgren et al 2009). The arcs are called evening anticorrelation arcs (Marklund 1984), growth phase arcs (Haerendel 2010;Lyons et al 2011;, preexisting arcs (Jiang et al 2012), and quiet evening arcs (Coroniti and Pritchett 2014). Hereinafter, we refer it to as a quiet arc.…”
Section: Growth Phasementioning
confidence: 99%
“…Precipitating electrons with a peak energy of~1-5 keV are thought to cause the quiet arc, suggesting that the electrons are accelerated by the field-aligned electric field (Meng 1976;Lassen et al 1977;Haerendel et al 2012) in the region of the upward field-aligned current (FAC) (Haerendel et al 2012;Jiang et al 2012). The upward FAC associated with the quiet arc is thought to originate from an azimuthal gradient in the plasma pressure near midnight (Lyons and Samson 1992;Antonova 1993;Stepanova et al 2002;Haerendel 2008;Coroniti and Pritchett 2014). Using the REPPU code, Tanaka (2015) proposed that the quiet arc is generated by the FAC associated with flow shear in the Y-direction of the high-latitude magnetosphere.…”
Section: Growth Phasementioning
confidence: 99%
“…This flow shear is consistent with the convergence of the Pedersen currents (the converging electric field [ Johnson et al ., ]) that are connected with the upward FAC in the ionosphere. The quiet arcs are known by a number of different names, including evening anticorrelation arcs [ Marklund , ], growth phase arcs [ Lyons et al ., , ; Haerendel , ; Nishimura et al ., ], preexisting arcs [ Jiang et al ., ], and a quiet evening arcs [ Coroniti and Pritchett , ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the near‐Earth plasma sheet has been believed to be the generation region for the FACs. By considering the necessary current continuity, azimuthal pressure gradients in the near‐Earth plasma sheet may act to generate and close the upward FACs that are associated with the quiet arcs [ Lyons and Samson , ; Antonova , ; Stepanova et al ., ; Haerendel , ; Coroniti and Pritchett , ]. To explain the narrowness of the quiet arcs, Galperin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation